2016
DOI: 10.1111/wvn.12159
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Self‐Management Barriers and Self‐Efficacy in Chinese Patients with Type 2 Diabetes: The Mediating Role of Appraisal

Abstract: Diabetes appraisal plays a mediating role in the association between self-management barriers and self-efficacy in patients with type 2 diabetes. Reflecting on patients' appraisal of diabetes can help to develop evidence-based and patient-centered interventions. Interventions that enhance individuals' positive appraisal of diabetes have the potential to buffer the negative effects of self-management barriers on self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…32 On the other hand, persons with low self-efficacy are less likely to participate in problem-solving actions and have high levels of resistance on medication usage and healthy eating. 8 Negotiating behavioural change by setting personal goals, action planning and reflecting to help persons work through ambivalence, was a key concept of persons' empowerment intervention programmes. Strategies such as the above can be useful to enhance persons' commitment to diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 On the other hand, persons with low self-efficacy are less likely to participate in problem-solving actions and have high levels of resistance on medication usage and healthy eating. 8 Negotiating behavioural change by setting personal goals, action planning and reflecting to help persons work through ambivalence, was a key concept of persons' empowerment intervention programmes. Strategies such as the above can be useful to enhance persons' commitment to diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies such as the above can be useful to enhance persons' commitment to diabetes self-management. 8 It is known that chronic illnesses, such as DM, require intensive care, both by healthcare professionals and by the patients themselves. Observational studies have shown that adherence to healthy lifestyle behaviours is associated with substantially reduced risks of CVD, complications and death in people with DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar with the other pilot of diabetes education in mainland China (Fu et al, ). Diabetes knowledge lays the basis of behaviour change for patients with T2DM, and self‐efficacy was positively associated with diabetes self‐management behaviours (Cheng, Sit, Leung, & Li, ; Xu et al, ). Provider‐patient communication will indirectly affect diabetes self‐management behaviours through self‐efficacy as well (Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%